Analisis Kepuasan Konsumen terhadap Kualitas Pelayanan dengan Menggunakan Metode Customer Satisfaction Index dan Importance Performance Analysis Melalui Dimensi Servqual di PT. Tjakrindo Mas - Gresik - Abiyyu, Muhammad Rofi’; Suparto, Suparto (CV. Kalimasada Group, 2024)
The rapid development of technology and time changes have made competition between companies increasingly fierce. It also happens in the HDPE PVC pipe industry, highlighting the importance of consumer assessment and consumer satisfaction. To achieve the company's success, Tjakrindo Mas Ltd. must understand consumer behavior, especially what consumers need or want. In addition, improving the quality of products and services becomes a concern for this company to realize the company's vision and mission, such as by maintaining and increasing market share. However, this company still has a decline in turnover in sales of PVC and HDPE pipes due to the large number of competitors who are almost similar to it. Therefore, this research aims to determine the attributes of services and improve service performance in the future by applying the Customer Satisfaction Index and Importance Performance Analysis methods. The results of the research indicated that customer satisfaction at Tjakrindo Mas Ltd. obtained a CSI value of 77.22%, or satisfactory. Furthermore, it reached an IPA value of 97.5%, meaning that it met consumer expectations